Arthroscopic 3‐Tunnel Suture‐Bridge Technique for Treating Tibial Avulsion Fractures of the Posterior Cruciate Ligament Is Associated With Excellent Clinical and Radiological Outcomes - Zhiqiang Ren; Mingquan Liu; Chen Youxia; Zhaoyu Wu; Zhou Zhang; Zhong Li; Juncai Liu (Arthroscopy, 2026)
Purpose To evaluate the clinical effectiveness of an all‐arthroscopic 3‐tunnel suture‐bridge technique that employs anterior, posteromedial, and posterolateral tibial tunnels to generate a triangulated suture‐bridge construct for stable fixation of the avulsed fragment, with a focus on functional recovery, knee stability, and radiographic healing. Methods A retrospective analysis was conducted on patients who underwent all‐arthroscopic 3‐tunnel suture‐bridge fixation for posterior cruciate ligament (PCL) tibial avulsion fractures between January 2020 and June 2023. Patients were included if they had a radiologically confirmed PCL tibial avulsion fracture and completed a minimum of 24 months of follow‐up. Knee function was assessed using range of motion, International Knee Documentation Committee (IKDC) subjective score, Lysholm knee score, and Tegner activity scale; knee stability was evaluated using KT‐1000 measurements of posterior tibial translation; and fracture reduction and healing were assessed using postoperative radiographs and computed tomography. Results Between January 2020 and June 2023, a total of 33 patients with PCL tibial avulsion fractures were assessed. According to the predefined inclusion and exclusion criteria, 22 patients (13 men and 9 women; median age 27.5 years, range 15‐55 years) were finally included in the study and completed a minimum follow‐up of 24 months (range, 24‐40 months). Significant postoperative improvements were observed in range of motion, IKDC subjective score, Lysholm knee score, and Tegner activity scale compared with preoperative values (all P < .001). At the patient level, all patients achieved or exceeded the cohort‐specific minimal clinically important difference thresholds for the IKDC subjective score, Lysholm knee score, and Tegner activity scale at both 1 year postoperatively and at the final follow‐up. KT‐1000 measurements of posterior tibial translation improved from 8.4 ± 1.3 mm preoperatively to 2.9 ± 0.7 mm at the final follow‐up ( P < .001). Postoperative radiographs and computed tomography confirmed immediate anatomic reduction and complete bony union within 3 months. Conclusions Arthroscopic 3‐tunnel suture‐bridge fixation for PCL tibial avulsion fractures resulted in significant improvement in knee function and stability at a minimum 2‐year follow‐up. Radiographic evaluations confirmed satisfactory anatomic reduction and osseous healing, with no procedure‐related complications observed. In addition, all patients achieved the minimal clinically important difference thresholds for the Lysholm knee score, IKDC subjective score, and Tegner activity scale, indicating clinically meaningful functional improvement. Level of Evidence Level IV, retrospective case series.